Effect of counseling on breast feeding practices - Rai, Preeti Lata; Sharma, Neetu; Gaur, Ajay; Shingwekar, A G (Indian Journal of Child Health, 2014)
Background: National Family Health Survey-3 data show that the initiation of breastfeeding within 1 h is only24.5%, whereas the exclusive breastfeeding rates in children